STRATEGI COLLABORATIVE COMMUNICATION DALAM MENCEGAH KONFLIK KEPENTINGAN PENGELOLAAN WISATA OKSIGEN GILI IYANG - Arifin, Syamsul; Tini, Dwi Listia Rika; Azinuddin, Muaz; Rachmad, Teguh Hidayatul; Triandika, Lulus Sugeng (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
The development of Gili Iyang as a new tourist destination has quite complex problems, one of which is due to mutual claims to the oxygen location point between the people of Bancamara Village and Banraas Village. Therefore, this research aims to prevent conflicts of interest between the two villages using a collaborative communication approach. This research uses qualitative methods, including observation and interview data collection methods. The results of this study show that 1) The collaboration process can occur through open communication. 2) Conflict prevention of Gili Iyang tourism management can be done through several stages: consensus, mediation, deliberation, peace declaration, and direct perception. 3) The role of collaborative communication in the joint management of Gili Iyang tourism is based on the willingness to share understanding, open dialog, commit to goals, and build trust. 4) A collaborative communication strategy is built dynamically to increase participation and willingness to build a shared understanding of the importance of joint management.